Hubungan Paparan Whole Body Vibration Dengan Low Back Pain Pada Pengemudi Ojek Online - Tena Djuartina; Anthony Yauwono; Robi Irawan; Andreas Steven (Majalah Kedokteran Indonesia, 2020)
Introduction: Low back pain is a condition characterized by pain and stiffness on lumbosacral region. Whole body vibration is a mechanical vibration transmitted to whole body. Whole body vibration is a risk factor for low back pain. To determine the relationship of whole body vibration with low back pain.Method: Using cross-sectional method for 27 online ojek driver in Jakarta. Respondent filled the Nordic Musculoskeletal Questionnaire (NMQ). Vibration from the motorcycle measured with smartphone application. Data analysis using Fisher Exact test.Result: There are seven respondent with LBP and vibration exceeding ELV, four respondent with LBP and vibration not exceeding ELV, four respondent without LBP and vibration not exceeding ELV and 12 respondent without LBP and vibration not exceeding ELV.Conclusion: There is correlation between whole body vibration and low back pain.